Transcriptome Profiling Reveals the Effects of Rootstocks on Scion Architecture in Malus domestica Borkh Var. ‘Harlikar’ - Bin Xie; Junhao Li; Jiangtao Zhou; Guodong Kang; Zhongwen Tang; Xiaojian Ma; Xin Li; Jing Wang; Yanzhen Zhang; Yanhui Chen; Sumiao Yang; Cungang Cheng (Plants)
Rootstocks largely determine the tree architecture of the grafted scions, significantly affects yield, suitability for mechanical harvesting, and planting pattern of apple orchards. It is thus important to reveal the mechanisms behind the rootstocks influence on the tree architecture of scions in apple trees. This study analyzed the grafting survival rate, the physiological parameters including plant growth, photosynthesis and nutrient accumulation in the apple variety ‘Harlikar’ with eight apple rootstocks. We also explored the mechanism of scion architecture formation using transcriptomics based on different scion/rootstock combinations. The results indicated that ‘Harlikar’ had the lowest grafting survival rate with rootstock ‘M26’, with less callus formed at the graft interface, foliage etiolation, and weak photosynthetic capacity. While ‘Harlikar’ had better affinities with ‘M9-T337’, ‘M9-Nic29’, ‘M9-Pajam2’, ‘B9’, ‘71-3-150’, ‘Qingzhen 2’, and ‘Malus baccata’. Among these, the highest plant height and the highest number of lateral branches were observed in ‘Harlikar’ with rootstock ‘Qingzhen 2’, they were 1.12-times and 2.0-times higher than ‘Harlikar’ with vigorous rootstock ‘M. baccata’, respectively. The highest accumulations of total nitrogen, total phosphorus, and total potassium in scions were observed in ‘Harlikar’/‘Qingzhen 2’, they were 2.22-times, 2.10-times, and 11.80-times higher than that in ‘Harlikar’/‘M. baccata’. The lowest plant height was observed in ‘Harlikar’/‘71-3-150’, only 50.47% of ‘Harlikar’/‘Qingzhen 2’ and 56.51% of ‘Harlikar’/‘M. baccata’, and the lowest internode length was observed in ‘Harlikar’/‘M9-Nic29’, only 60.76% of ‘Harlikar’/‘Qingzhen 2’ and 79.11% of ‘Harlikar’/‘M. baccata’. The transcriptome, weighted gene co-expression network and KEGG enrichment analyses revealed that, compared to ‘Harlikar’/‘M. baccata’, most differentially expressed genes screened from ‘Harlikar’/‘Qingzhen 2’, ‘Harlikar’/‘71-3-150’, and ‘Harlikar’/‘M9-Nic29’ were enriched in hormone signal transduction pathways. Specifically, auxin-repressed protein gene ARP, cytokinin synthesis related genes CKXs and CYP92A6, and brassinosteroid synthesis related gene CYP87A3 were involved in the dwarfing of ‘Harlikar’/‘71-3-150’ and ‘Harlikar’/‘M9-Nic29’. Cytokinin synthesis related gene ARR-A and abscisic acid-responsive element binding factor gene ABF were the key to increased branching in ‘Harlikar’/‘Qingzhen 2’. In addition, acid phosphatase genes ACPs, and serine/threonine-protein kinase genes PBLs were involved in the vegetative growth of scions in ‘Harlikar’/‘Qingzhen 2’ by affecting the absorption and utilization of nutrients. These results provide theoretical guidance for cultivating high-quality ‘Harlikar’ apple trees and elucidate the molecular mechanisms regulating plant height and lateral branch formation in apple.